Distribution management - Aciento, Marife Agustin; Aciento, Gilfred Abad (Manila, 2019)
This book will help the students prepare on the changing and challenging career in business with appropriate marketing attitudes and competencies.
Keywords: Marketing channels; Physical distribution of goods - management